Indirect methods of therapeutic compliance ratings - Limaylla, Maribel L. (2017)
The bibliographycal review of indirect methods of assessment of adherence to therapeutic was performed, in order to publicize to health professional available strategies that can be helpful to achieve the effectiveness of prescribed treatment; whenever such methods are applicable in the clinical interview with patient in daily work, especially of physician.